Readout electronics for CBM-TOF super module quality evaluation based on 10 Gbps ethernet. (27th July 2017) - Jiang, D.; Cao, P.; Huang, X.; Zheng, J.; Wang, Q.; Li, B.; Li, J.; Liu, S.; An, Q.
Abstract: The Compressed Baryonic Matter-Time of Flight (CBM-TOF) wall uses high performance of Multi-gap Resistive Plate Chambers (MRPC) assembled in super modules to identify charged particles with high channel density and high measurement precision at high event rate. Electronics meet the challenge for reading data out from a super module at high speed of about 6 Gbps in real time. In this paper, the readout electronics for CBM-TOF super module quality evaluation is proposed based on 10 Gigabit Ethernet. The digitized TOF data from one super module will be concentrated at the front-end electronics residing on the side of the super module and transmitted to an extreme speed readout module (XSRM) housed in the backend crate through the PCI Express (PCIe) protocol via optic channels. Eventually, the XSRM transmits data to the data acquisition (DAQ) system through four 10 Gbps Ethernet ports in real time. This readout structure has advantages of high performance and expansibility. Furthermore, it is easy to operate. Test results on the prototype show that the overall data readout performance for each XSRM can reach up to 28.8 Gbps, which means XSRM can meet the requirement of reading data out from 4 super modules with 1280 channels in real time.